2014
DOI: 10.3130/jaabe.13.373
|View full text |Cite
|
Sign up to set email alerts
|

Spatial Configuration of Japanese Elementary Schools: Analyses by the Space Syntax and Evaluation by School Teachers

Abstract: In this paper, we analyzed the spatial configuration of Japanese elementary schools by using the space syntax theory. First, we selected the floor plans of 76 Japanese elementary schools from an architectural journal and educational government offices and analyzed them. They were classified into five types according to the spatial connection properties of mean integration, mean connectivity, and intelligibility. Second, they were classified into five types by the order of the integration of different functiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 16 publications
0
3
0
Order By: Relevance
“…It presents a grid over the spaces to be analyzed and investigates the visibility relationships of every point in the grid to every other point. The theory of isovist and space syntax (Hillier and Hanson, 1984) -a theory often used in previous studies (Choi et al, 2013, Kishimoto andTaguchi, 2014) to validate the relationships among spaces -was combined with VGA, and one important result of the combination was 'connectivity.' Connectivity in VGA is "how many locations each node can see" ( (Turner, 2001), page 10); it is the number of grids that are visible from a point, and it is related to the primary isovist concept.…”
Section: Visibility In Spacesmentioning
confidence: 99%
“…It presents a grid over the spaces to be analyzed and investigates the visibility relationships of every point in the grid to every other point. The theory of isovist and space syntax (Hillier and Hanson, 1984) -a theory often used in previous studies (Choi et al, 2013, Kishimoto andTaguchi, 2014) to validate the relationships among spaces -was combined with VGA, and one important result of the combination was 'connectivity.' Connectivity in VGA is "how many locations each node can see" ( (Turner, 2001), page 10); it is the number of grids that are visible from a point, and it is related to the primary isovist concept.…”
Section: Visibility In Spacesmentioning
confidence: 99%
“…The results show that there is an indirect relationship between the step depth of the spaces of the classrooms and the tendency of students (especially of lower grades) to spend their break times in those spaces. In another study, Kishimoto and Taguchi [45] studied 76 primary schools in Japan and found that spatial layouts with a higher rate of intelligibility generate more contact and interaction between students of different grades. Pasalar [46,47] found that the spatial configuration of school buildings affects patterns of interaction and movement.…”
Section: Research Literaturementioning
confidence: 99%
“…First, the interior areas of elementary schools need to be investigated. Previous studies (Kishimoto and Taguchi, 2014) have emphasized the influence of schools' indoor environments on the welfare of students. In addition, despite the significant amount of time students spend in these areas, few environmental criminology studies have focused on these environments.…”
Section: Introductionmentioning
confidence: 99%